Optimum BMI cut points to screen asian americans for type 2 diabetes - Araneta, Maria Rosario G; Kanaya, Alka M; Hsu, William C; Chang, Healani K; Grandinetti, Andrew; Boyko, Edward J; Hayashi, Tomoshige; Kahn, Steven E; Leonetti, Donna L; McNeely, Marguerite J; Onishi, Yukiko; Sato, Kyoko K; et al. (Diabetes care, 2015)
Asian Americans manifest type 2 diabetes at low BMI levels but may not undergo diagnostic testing for diabetes if the currently recommended BMI screening cut point of ≥25 kg/m(2) is followed. We aimed to ascertain an appropriate lower BMI cut point among Asian-American adults without a prior diabetes diagnosis. We consolidated data from 1,663 participants, ages ≥45 years, without a prior diabetes diagnosis, from population- and community-based studies, including the Mediators of Atherosclerosis in South Asians Living in America study, the North Kohala Study, the Seattle Japanese American Community Diabetes Study, and the University of California San Diego Filipino Health Study. Clinical measures included a 2-h 75-g oral glucose tolerance test, BMI, and glycosylated hemoglobin (HbA1c). Mean age was 59.7 years, mean BMI was 25.4 kg/m(2), 58% were women, and type 2 diabetes prevalence (American Diabetes Association 2010 criteria) was 16.9%. At BMI ≥25 kg/m(2), sensitivity (63.7%), specificity (52.8%), and Youden index (0.16) values were low; limiting screening to BMI ≥25 kg/m(2) would miss 36% of Asian Americans with type 2 diabetes. For screening purposes, higher sensitivity is desirable to minimize missing cases, especially if the diagnostic test is relatively simple and inexpensive. At BMI ≥23 kg/m(2), sensitivity (84.7%) was high in the total sample and by sex and Asian-American subgroup and would miss only ∼15% of Asian Americans with diabetes. The BMI cut point for identifying Asian Americans who should be screened for undiagnosed type 2 diabetes should be <25 kg/m(2), and ≥23 kg/m(2) may be the most practical.